A Note οn the Impacts of the 1810 Seismic Sequence on Crete - Stiros, Stathis; Horsch, Georgios (Bulletin of the Geological Society of Greece, 2022)
An intermediate depth earthquake sequence with an unusually strong aftershock hit Crete in 1810 and was felt in a very broad area. This seismic sequence was believed to have caused a death toll of about 2000-3000 and destroyed a major part of houses in the wider Heraklion area. In this article we present an unpublished note for this earthquake sequence from the memoirs of Frangiskos Limbritis, military and political personality in Crete, and analyze certain other notes from Crete and conclude that the death toll in Heraklion which was mainly affected was of the order of 300 and that structural damage was smaller than what believed in the past and was mostly rapidly repaired, especially in the meizoseismal area which roughly covers the present-day Heraklion prefecture (max intensities VIII-IX).